High-performance liquid chromatographic determination of some polar phospholipids in serum - Böswart, J; Schmidt, T; Kostiuk, P; Pacáková, V; Stulík, K (Journal of chromatography, 1989)
The experimental conditions have been optimized for high-performance liquid chromatographic determination of phosphatidylethanolamine (PE), phosphatidylcholine (PC) and sphingomyelin (SM) in serum. The phospholipids are separated on a silica gel column, using a mobile phase of acetonitrile-methanol-water (100:10:18, v/v), with ultraviolet photometric detection at 200 nm. The limit of detection was 0.2 micrograms (in 20 microliters) for natural phospholipids and 2.5 micrograms for synthetic phospholipids; the relative standard deviation was ca. 5%. An alternative detection is tensammetry at a mercury electrode, at a potential of -1.8 V, with an a.c. current frequency of 60 Hz and an amplitude of 20 mV. The tensammetric detection has an advantage in its independence of the structure of the phospholipids. In measurements without a column (flow-injection analysis), the tensammetric detection also yields a somewhat lower limit of detection than photometry (0.15 micrograms per 20 microliters), but this value increases more than ten times in chromatographic detection. The precision is poorer and is more susceptible to interferences. The method was applied to the determination of the above substances in the blood of obese children, as a function of physical stress and spa treatment. It was shown that physical exercise causes a decrease in the contents of PE and PC in the patients. On the other hand, the spa treatment has no pronounced effect on the phospholipid content in the blood.
Keywords: Phospholipids; fosfolipidy; Chromatography, High Pressure Liquid; lidé; mladiství; Adolescent; Spectrophotometry, Ultraviolet; elektrochemie; Humans; spektrofotometrie ultrafialová; Electrochemistry; Male; mužské pohlaví; vysokoúčinná kapalinová chromatografie; ženské pohlaví; Female